Improving Mathematics Achievement and Interest through Joyful Teaching: Evidence from Seventh-Grade Girls in Kabul - Abdul Maroof Mashal; Wahidullah Enayat; Rahmatullah Qarloq; Abdul Munir Khirzada (Jurnal Educative: Journal of Educational Studies, 2026)
This study examined the effect of joyful teaching methods on seventh-grade female students’ mathematics learning and interest compared with traditional instruction. A quasi-experimental pre-test–post-test control group design was used. The study was conducted with 68 seventh-grade female students in Kabul, Afghanistan, divided into an experimental group taught through joyful teaching methods and a control group taught through traditional instruction. Each group included 34 students. Data were collected using a mathematics achievement test and a student opinion questionnaire on interest and attitudes toward mathematics. Descriptive statistics, paired-samples t-tests, mean gain, percentage improvement, approximate effect size, difference-in-differences, and normalized learning gain were used to analyze the results. The findings showed that both groups improved after instruction; however, the joyful teaching group demonstrated stronger learning gains. The mean score of the joyful teaching group increased from 15.11 to 18.52, while the traditional teaching group increased from 14.91 to 16.17. The joyful teaching group showed a higher mean gain (3.41 vs. 1.26), greater percentage improvement (22.57% vs. 8.45%), and a larger approximate effect size (r = 0.77 vs. r = 0.38). The performance gap between the two groups increased from 0.20 at pre-test to 2.35 at post-test in favor of the joyful teaching group. Questionnaire findings also indicated that students taught through joyful methods reported more positive attitudes, greater interest, stronger participation, and higher satisfaction in learning mathematics. Overall, the results suggest that joyful teaching can be an effective, low-cost, and student-centered approach for improving both mathematics achievement and students’ interest in mathematics.